(untitled) (Journal of Veterinary Medicine and Animal Production, 2022)
This study showed herd strcuture and husbandry practices in 60 dairy farms at different preurban areas of Khartoum, Khartoum North and Omdurman of Khartoum State (20 farms from each town). Information about dairy management was collected by questionnaire and direct interview with farms’ owners. The results indicated that there were significant (P < 0.05) differences in education levels of dairy farms’ owners. Dairy farms’ owners in Khartoum exhibit higher illiteracy level (35%), compared to those in Khartoum North (15%) and Omdurman (30%). Significant (P< 0.05) differences were obtained in herds size and herds structure. Moreover, dairy herd numbers were 170.25± 72.83, 123.10± 105.71 and 92.35± 29.23 in Khartoum North, Khartoum and Omdurman, respectively. Breed type revealed non-significant differences between the three cities. However, 92% of the cattle in the studied farms were grade cattle and mainly they were of unknown foreign blood percentages. Ideal building materials, design and management practices rarely practiced in preurban dairy farms at Khartoum (45%) and Khartoum North (30%). Corrugated iron roof, concrete flour, teats dipping in antiseptics and machine milking were reported to be very rare. The present study concluded that the majority of farms were poorly constructed and they are with limited management skills. This might create health risk and environemental contaminations. Hence provision of essential services and extension services among dairy farmers, labours and milkers were urgently needed on best dairy faming practices such as housing, milking and general hygiene.